2003
DOI: 10.1007/s00705-003-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional mapping in Chilo iridescent virus infections

Abstract: Chilo iridescent virus (CIV) belongs to the family Iridoviridae, which are icosahedral cytoplasmic DNA viruses with large, linear, and circularly permuted genomes. Previous studies on infected-cell-specific polypeptides suggested temporal regulation of CIV gene expression. Recently, we demonstrated three temporal classes at the transcriptional level, in CIV infections of a spruce budworm cell line. We also demonstrated a transcriptional cascade with positive and negative control. In this paper, we assign all d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…In these studies, the second class is called delayed-early. For example, in CIV infection, 37 transcripts were classified as IE, 35 transcripts as DE, and 65 transcripts as L (12). Thus, the temporal expression kinetics observed in RSIV are similar to those observed in other iridoviruses, suggesting that they are a common feature of the family Iridoviridae.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…In these studies, the second class is called delayed-early. For example, in CIV infection, 37 transcripts were classified as IE, 35 transcripts as DE, and 65 transcripts as L (12). Thus, the temporal expression kinetics observed in RSIV are similar to those observed in other iridoviruses, suggesting that they are a common feature of the family Iridoviridae.…”
Section: Discussionsupporting
confidence: 55%
“…These results are similar to those observed in other members of the family Iridoviridae. IE transcripts of CIV were also not clustered in any specific regions in the CIV genome, DE transcripts were clustered in at least three DE discrete regions, and L transcripts were distributed throughout the genome (12). IE transcripts originated from at least one third of the genome in FV3 (57) and from seven different regions in Wiseana iridescent virus (36).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Other intergenic regions did not contain lower GϩC peaks, indicating that two types of putative intergenic regions were present in SfAV: GϩC-rich and GϩC-poor regions. Data published previously on transcription of CIV indicate that genes are transcribed temporally as mono-or polycistronic mRNA (31), suggesting that the GϩC-poor regions delineate regions in which transcription is arrested at the termination of mRNA synthesis. In agreement with previous ascovirus sequence analyses (97), we observed that all GϩC-poor regions contained short inverted repeats that might function as transcription termination signals.…”
Section: Vol 80 2006mentioning
confidence: 89%